Citizen participation in urban policy: Lessons based on Berlin and S\~ao Paulo experiences - Mariana Morais (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
This paper explores how different means of citizen participation influence urban policies at the city level. The study considers four case studies in two cities, Berlin, Germany and Sao Paulo, Brazil, covering different stages of the policy cycle. Informed by the assessment of qualitative research conducted during a year-long study, the experiences illustrate that the ability to navigate between streets and institutions in participatory procedures is key to ensuring political embeddedness of citizen contributions while remaining context sensitive. By expanding the concept of participation to incorporate different fields of action, the study provides a lens to inform procedural designs while questioning frameworks that hinder the democratic urban transformation.
Keywords: 320; Citizen participation; participatory planning; participatory design; democraticcities